Citizenship and democratization in Southeast Asia - Berenschot, Ward.; Schulte Nordholt, Henk, 1953-; Bakker, Laurens Gerrit Hendrik, 1974-; Porio, Emma. (Social, Economic and Political Studies of the Middle East and Asia, 2017)
Citizenship and Democratization in Southeast Asia redirects the largely western-oriented study of citizenship to postcolonial states. Providing various fascinating first-hand accounts of how citizens interpret and realize the recognition of their property, identity, security and welfare in the context of a weak rule of law and clientelistic politics, this study highlights the importance of studying citizenship for understanding democratization processes in Southeast Asia. With case studies from Thailand, Indonesia, the Philippines and Cambodia, this book provides a unique bottom-up perspective on the character of public life in Southeast Asia. Contributors are: Mary Austin, Laurens Bakker, Ward Berenschot, Sheri Lynn Gibbings, Takeshi Ito, David Kloos, Merlyna Lim, Astrid Norén-Nilsson, Oona Pardedes, Emma Porio, Apichat Satitniramai, Wolfram Schaffer and Henk Schulte Nordholt. This title is available in its entirety in Open Access .